COUNSELING ON PREVENTION OF TUBERCULOSIS TRANSMISSION IN FAMILIES AT THE CARE HEALTH CENTER IN KOTABLANGKEJEREN - sembiring, bungamari; Lubis, Fithri Handayani (INSTITUT KESEHATAN DELI HUSADA, 2024)
The conduct of pulmonary TB patients strongly influences the transmission of pulmonary TB disease, since if patients cough and sneeze they might infect persons around them through air containing germs or splashes of phlegm containing germs. This research is a type of analytical observational research using a cross sectional design. This research will be carried out at the Blangkejeren City Care Health Center. The research period will be carried out from December 2023 to May 2024. The population in this study is all pulmonary TB sufferers in the Blangkejeren City Care Health Center Work Area, with a total of 41 participants. The sample approach employed in this research was total sampling The management of the Blangkejeren City Health Care Center is expected to be able to utilize smartphones and social media as communication media with Pulmonary Tuberculosis patients to more easily remind patients about the Prevention of Pulmonary Tuberculosis Transmission which must be carried out daily so that the patient's attitude will be better and they are also expected to be able to carry it out routinely. educational activities for families of Pulmonary Tuberculosis patients regarding Prevention of Transmission of Pulmonary Tuberculosis so that families can also remind patients when doing activities at home.